2020
DOI: 10.1111/jtxs.12558
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of milk composition and milking season on quality characteristics of chhana

Abstract: The quality characteristics of chhana varied due to the milk composition (cow‐, buffalo‐, and mixed‐ milk) which in turn was affected by the milking season (summer and winter). Upon heating and acidification of milk samples water holding phenomena and denatured protein association within and with other components lead to variation in both macroscale properties (color, texture, and rheology) and molecular bonding patterns (FTIR character). Yield, lightness (L* value), textural firmness, and elastic modulus of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Hardness increased as the level of SMP increased in the blends for CM and BM. Chakraborty et al (2020) reported that higher protein content of milk led to more protein-protein interactions and hence resulted in a firmer protein network for the Paneer microstructure. Likewise, fat interrupts the formation of a stronger casein matrix in Paneer; thus, as the fat content of milk increases, firmness of Paneer decreases.…”
Section: Texture Of Different Types Of Paneermentioning
confidence: 99%
“…Hardness increased as the level of SMP increased in the blends for CM and BM. Chakraborty et al (2020) reported that higher protein content of milk led to more protein-protein interactions and hence resulted in a firmer protein network for the Paneer microstructure. Likewise, fat interrupts the formation of a stronger casein matrix in Paneer; thus, as the fat content of milk increases, firmness of Paneer decreases.…”
Section: Texture Of Different Types Of Paneermentioning
confidence: 99%